Novel inhibitor of bacterial sphingomyelinase, SMY-540, developed based on three-dimensional structure analysis. (June 2014) - Oda, Masataka; Imagawa, Hiroshi; Kato, Ryoko; Yabiku, Kenta; Yoshikawa, Tomomi; Takemoto, Takayuki; Takahashi, Hironobu; Yamamoto, Hirofumi; Nishizawa, Mugio; Sakurai, Jun; Nagahama, Masahiro
Abstract Context: Bacterial sphingomyelinase (SMase) is thought to play a crucial role in bacterial evasion of the immune response during the early stages of infections. Objective: The objective of this study was to predict the chemical structure required for competitive SMase inhibition, then synthesize and test the effect of potential inhibitors on the hydrolysis of sphingomyelin (SM) and protection against infection by Bacillus cereus. Materials and methods: We synthesized 10 potential SMase inhibitors, derivatives of RY221B-a analogues, based on predictions from three-dimensional structural analysis. We then tested the effect of these compounds on the inhibition of SM hydrolysis and protection of mice inoculated with B. cereus. Results: One compound, SMY-540, displayed a strong inhibitory effect (IC50 = 0.8 μM) upon SMase and prevented mortality in mice. Conclusion: SMY-540 is an effective inhibitor of Bc-SMase and has potential for use in the development of drugs to treat infectious diseases caused by bacteria that produce SMase.